Correlation between the surface morphology and structure and the photoluminescence of amorphous PbTiO3 thin films obtained by the chemical route - Pontes, F. M.; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Pizani, P. S.; Campos, CEM; Lanciotti, F. (Wiley-Blackwell, 2000)
A polymeric precursor method was used to synthesis PbTiO3 amorphous thin film processed at low temperature. The luminescence spectra of PbTiO3 amorphous thin films at room temperature revealed an intense single-emission band in the visible region, the visible emission band was found to be dependent on the thermal treatment history, Photoluminescence properties Versus different annealing temperatures were investigated. The experimental results (XRD, AFM, FL) indicate that the nature of photoluminescence (PL) must be related to the disordered structure of PbTiO3 amorphous thin films, Copyright (C) 2000 John Wiley & Sons, Ltd.
Keywords: luminescence; amorphous thin film; PbTiO3; surface morphology; atomic force microscopy